2004
DOI: 10.1016/j.rmed.2003.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of bronchial reactivity analysis in the diagnosis of bronchial asthma in patients with bronchial hyperresponsiveness

Abstract: We examined the usefulness of some bronchial reactivity indices to identify bronchial asthma in patients with airway hyperresponsiveness. Eighty-eight consecutive patients with positive response to histamine bronchial challenge (> or = 20% fall in FEV1) were included in the study. Dose-response curves were characterised by their sensitivity (PD20) and reactivity. Dose-response slope, continuous index of responsiveness (CIR) and bronchial reactivity index (BRI) with respect to baseline and post-diluent baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Bronchial hyperresponsiveness is a characteristic of asthma and provocative concentration causing a 20% fall in FEV1 (PC20_FEV1) derived from spirometry and two-point linear DRS are often used as parameters to determine BHR. 14,21,22) However, the conventional method is relatively hard to perform in young children and there have been previous studies comparing the conventional method and the IOS method; they suggested various cutoff points (such as PC40_Rrs6, 15) PC70_Rrs12, 23) and PC80_Xrs5 16) for diagnosing asthma as compatible for PC20_FEV1. In this study, we examined PC40_Rrs5 and PC80_Xrs5 in the classic asthma group and the CVA group.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial hyperresponsiveness is a characteristic of asthma and provocative concentration causing a 20% fall in FEV1 (PC20_FEV1) derived from spirometry and two-point linear DRS are often used as parameters to determine BHR. 14,21,22) However, the conventional method is relatively hard to perform in young children and there have been previous studies comparing the conventional method and the IOS method; they suggested various cutoff points (such as PC40_Rrs6, 15) PC70_Rrs12, 23) and PC80_Xrs5 16) for diagnosing asthma as compatible for PC20_FEV1. In this study, we examined PC40_Rrs5 and PC80_Xrs5 in the classic asthma group and the CVA group.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three bronchial reactivity indices analysed, BRI shows the closest relationship with HRQL (table 3). It has previously been shown to discriminate better than DRS or CIR between subjects with or without asthma with AHR 19. It is possible that the BRI's closer to normal distribution confers on it a greater discriminating capacity when compared with the other indices of bronchial reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the sensitivity analysis, bronchial reactivity seems to more adequately reflect the severity of the response, as it assesses the intensity of the bronchoconstriction 17 18. In addition, it has been shown to be more useful in identifying patients with asthma19 and in maintaining a better relationship with the degree of oxidative stress of these patients 20…”
Section: Introductionmentioning
confidence: 99%
“…Linear regressions (adjusted on variables that differed between groups) were used to test for obesity‐group effects at five levels: (i) baseline values, (ii) sensitivity as measured by the PD20 for each patient, 26–28 (iii) percent responsiveness values at the end of methacholine testing (PD20 percent change values, also known as airway responsiveness), (iv) the closing index (% change in FVC/% change in FEV1) 16 and (v) percent reversibility.…”
Section: Methodsmentioning
confidence: 99%
“…CT, computed tomography; FEV1, forced expiratory volume in 1 second; FVC, forced vital capacity Spirometry in a seated position Spirometry in a supine position FVC ≥ 90% of seated position? Spirometry in a supine position Isotonic saline nebulization CT First dose of methacholine Spirometry in a supine position FEV1 and FVC ≥ 80% of seated position?Linear regressions (adjusted on variables that differed between groups) were used to test for obesity-group effects at five levels: (i) baseline values, (ii) sensitivity as measured by the PD20 for each patient,[26][27][28] (iii) percent responsiveness values at the end of methacholine testing (PD20 percent change values, also known as airway responsiveness), (iv) the closing index (% change in FVC/% change in FEV1)16 and (v) percent reversibility.…”
mentioning
confidence: 99%